APPLICATION OF THE SIAKAD ONLINE SIKUM-K13 BASED ON WEB AND ANDROID MOBILE FOR ELEMENTARY SCHOOL TEACHERS - Hartatik Hartatik; Agus Purnomo (Yayasan Education and Social Center, 2022)
The curriculum applicable in the Indonesian Education System implemented by the government is updated according to needs. The curriculum applies as an independent learning curriculum in the 2013 curriculum. The 2013 curriculum has four aspects of assessment, namely knowledge aspects, skills aspects, attitude aspects, and behaviours. In the 2013 Curriculum, there are streamlined and added materials, especially in the learning materials. The streamlined material is seen in Indonesian, social studies, and PPKn, while mathematics is added. Many of the problems faced in the implementation of the 2013 curriculum are due to several factors as follows: 1) The difficulty of changing the mindset of teachers, 2) Changes in the learning process from teacher-centred to student-centred, 3) low spiritual morals, reading and research culture is still low 4) Lack of IT mastery by teachers 5) weak mastery of the administrative field, 6) tendency of teachers to emphasize more cognitive aspects. For this reason, in this service, they carried out training on applying the siakad online curriculum 2013